Can Judges Make a Difference? The Scope for Judicial Decisions on Climate Change in New Zealand Domestic Law - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2018)
Political decision-making is at the heart of decisions on both mitigation and adaptation for climate change. While the norms are established internationally, they must be translated into domestic law in order to have bite. The making and enforcement of domestic law in many areas of environmental protection are frequently less than optimal. Legislation takes time to design and to enact. The details matter a great deal. Laggard governments around the world have been subjected to judicial review on their climate change policies. Furthermore, all statutes are subject to interpretation by courts. Administrators can and do make mistakes that are corrected by authoritative judicial interpretation. With particular emphasis on New Zealand law, this article will examine the degree to which judicial decisions can correct and encourage government policies on climate change and give them a "nudge" towards making them effective. The potential role of the Waitangi Tribunal will also be mentioned and the Parliamentary Commissioner for the Environment. The issue of whether constitutional protection for the environment, with application to climate change, could be useful will be canvassed.